PENGARUH HARGA TERHADAP MINAT BELI SKINCARE MS GLOW: (STUDI KASUS PADA MAHASISWA PROGRAM STUDI SARJANA TERAPAN ADMINISTRASI BISNIS POLITEKNIK NEGERI AMBON) - Femilia Christin Sopakua; Maudy Marla Tanihatu; Saul Ronald Jacob Saleky; Stenly Ronaldo Titioka (Jurnal Administrasi Terapan, 2024)
ABSTRACTThe beauty business, including skincare, is increasingly becoming a trend today. One such example is MS Glow skincare, a local brand known for its good quality, especially regarding health and safety in usage. However, the phenomenon observed is that this skincare has not been able to reach all market segments due to its relatively high price. One of the segments facing purchasing challenges includes students, such as those in the Applied Bachelor's Degree Program in Business Administration, Department of Business Administration, Ambon State Polytechnic. Price is a significant factor contributing to the low purchase interest in MS Glow skincare products. The objective of this study is to determine the effect of price on the purchase interest in MS Glow skincare products among students of the Applied Bachelor's Degree Program in Business Administration, Department of Business Administration, Ambon State Polytechnic. A sample of 79 respondents was taken using probability sampling with a purposive sampling approach, where respondents selected must have previously used skincare products. This study uses a simple linear regression analysis method with SPSS software version 22, resulting in the regression equation Y = 4.916 - 0.239X. The hypothesis test results show a "t-value" of 2.769 with a probability of 0.005 (p<0.05), where the regression coefficient for variable X is -0.239. Based on these results, it can be concluded that Price has a negative and significant effect on the Purchase Interest in MS Glow skincare products among students of the Applied Bachelor's Degree Program in Business Administration, Department of Business Administration, Ambon State Polytechnic. Keywords: Price, Purchase Interest